Evaluation of HBsAg, anti-HCV, anti-HIV and VDRL test results in blood donors. Issue 4 (2011) - Deveci, Özcan; Tekin, Alicem; Günbay, Seda Sibel; Kılıç, Dilek; Kaygusuz, Sedat; Ağalar, Canan; Özer, Türkan Toka
No abstract available